2022
DOI: 10.3390/ijms23147852
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Workflow for the Label-Free Isolation and Genomic Analysis of Single Circulating Tumor Cells in Pancreatic Cancer

Abstract: As pancreatic cancer is the third deadliest cancer in the U.S., the ability to study genetic alterations is necessary to provide further insight into potentially targetable regions for cancer treatment. Circulating tumor cells (CTCs) represent an especially aggressive subset of cancer cells, capable of causing metastasis and progressing the disease. Here, we present the Labyrinth–DEPArray pipeline for the isolation and analysis of single CTCs. Established cell lines, patient-derived CTC cell lines and freshly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Although the concentration of CTCs is relatively low, making accurate separation of CTCs a great challenge, and its advantage over other liquid biopsy objects (such as ctDNA) is that CTCs are viable intact cells, which can accurately provide genomic information of cancer patients [ 32 ]. Recently, studies have isolated CTCs from pancreatic cancer patients and identified new single-cell copy number variations [ 33 ]. In addition, patient-derived CTCs cell lines can also be cultivated [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the concentration of CTCs is relatively low, making accurate separation of CTCs a great challenge, and its advantage over other liquid biopsy objects (such as ctDNA) is that CTCs are viable intact cells, which can accurately provide genomic information of cancer patients [ 32 ]. Recently, studies have isolated CTCs from pancreatic cancer patients and identified new single-cell copy number variations [ 33 ]. In addition, patient-derived CTCs cell lines can also be cultivated [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial single-cell microfluidic technologies are available, including the DEPArray (DiElectroPhoresis Array), [25] which manipulates single cells in a chamber using dielectrophoresis, and integrated fluidic circuits (IFC) which moves single cells into chambers using a system of pressure-controlled microfluidic valves. [26] Both technologies have been used in multiple studies to obtain single cell data, [27,28] but they suffer from limitations, such as lengthy processing time, lack of validation for use in live cells (DEPArray), and the ability to only collect a limited number of cells (IFC). [29,30] Droplet-based microfluidics can enable compartmentalization and analysis of analytes in a high throughput fashion.…”
Section: Introductionmentioning
confidence: 99%